[M.] IV Mégara y Theoc. XXIV. Algunas notas léxicas (Minerva, 2019)
This paper deals with the hapax and other terms rarely testified from [M.] IV Megara. Among them [M.] IV 27 αίνοτόκεια is of great interest, because it is an allusive reversal to Theoc. XXIV 73 αριστοτόκεια. A close reading of both poems also shows that the figures of Alcmena, Heracles and Ificles in [M.] IV are allusive reversals to the same characters of Theoc. XXIV. It allows us to suggest that it is wrong to assign the poet of Megara to the Homeric-Apollonian trend of Hellenistic Poetry as opposed to the Callimachean.